First molecular characterization of Cryptosporidium from three different points of two main rivers in Kuantan, Malaysia using 18S rRNA gene nested PCR - Barudin, Mohd Aiman; Md Isa, Muhammad Lokman; Othman, Noratikah; Mat Yusof, Afzan (Hainan Medical University, 2017)
Objective: To identify 18S ribosomal RNA partial sequences from three different points, namely downstream, midstream and upstream of two water rivers in Kuantan, Pahang, Malaysia Methods: In this study, a total of six water samples were collected from three different points of both Kuantan River and Balok River. Each water sample was processed and concentrated using continuous flow centrifuge (CFC) machine and purified using immunomagnetic separation (IMS) technique. Nested Polymerase Chain Reaction (nPCR) was applied to detect 18S ribosomal RNA sequence in those samples after DNA extraction. Genotyping and phylogenetic analysis were performed on the basis of 18S rDNA gene sequence of Cryptosporidium. Results: A total of five samples from six different points of both Kuantan River and Balok River were contaminated with Cryptosporidium. Only river water sample from the upstream point of Kuantan River was negative for Cryptosporidium. In this study, the sequencing results of five samples from both Kuantan River and Balok River belonged to Cryptosporidium parvum (C. parvum). Conclusions: To the best of our knowledge, this is the first report of C. parvum genotyping in both Kuantan River and Balok River by using molecular approach nested polymerase chain reaction (nPCR) on 18S ribosomal RNA gene.